2018
DOI: 10.37706/ijaz.v3i3.95
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Productive Zakat, Business Experience, and Mentoring on Farmers’ Revenues (Survey on Lumbung Desa Program by Sinergi Foundation in Cibaeud Village, Cigalontang District, Tasikmalaya Regency)

Abstract: This study aims to determine the effect of productive zakat, business experience and mentoring on the income of farmers participating in the Lumbung Desa-Sinergi Foundation program in Cibaeud Village, Cigalontang District, Tasikmalaya Regency. The research method used is an explanatory survey with a questionnaire as the data collection tool. The sampling technique is saturated sampling twith 68 respondents. Linear regression analysis is used as the data analysis technique. The results show that productive zaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, there is a difference in the effect of productive zakat on mustahiq. The research results of Taufiq et al (2018) also found that the assistance provided to mustahiq had a positive but insignificant effect. In a recent study, Kurniawan et al (2020) found that mentoring had a positive and significant effect on the development of mustahiq micro businesses.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, there is a difference in the effect of productive zakat on mustahiq. The research results of Taufiq et al (2018) also found that the assistance provided to mustahiq had a positive but insignificant effect. In a recent study, Kurniawan et al (2020) found that mentoring had a positive and significant effect on the development of mustahiq micro businesses.…”
Section: Introductionmentioning
confidence: 87%
“…The benefits of zakat felt by mustahiq can be seen from how much impact mustahiq feels like the beneficiary of zakat. The research results of Nafiah (2015) and Taufiq et al (2018) found that productive zakat has a positive and significant effect on mustahiq. Meanwhile, the latest research by Khumaini (2019) found that productive zakat funds have a positive and insignificant effect on the welfare of people.…”
Section: Introductionmentioning
confidence: 99%